Analysis of wear of cold forging dies using the technique of focal differentiation microscopy - Cwikla, Adam; Tofil, Arkadiusz (IEEE metrology for aerospace, 2019)
The paper presents the results of tests topography and surface roughness of dies used in the cold forging proces. Were tested two tools withdrawn from work due to cracks and abrasive wear. In the analyses has been used Alicona InfiniteFocus G5, the device based on the method of the focus variation microscopy. The principle of its operation and the possibilities of its use to accurately determine the topography and surface roughness tests of forging tools have been described. On the basis of the conducted tests, it has been found that the impressions are subject to a typical abrasive wear mechanism, which affects the change of their dimensions and surface roughness.